Literature of Review The Influence of Service Quality, Price, and Influencer Marketing on Netflix Users' Purchasing Decisions in Bekasi City - Yohannes Nevidelis Parhusip (Draf Solusi Indonesia, 2023)
This research is research with a literature review thatexamines the influence of service quality, price, andinfluencer marketing on purchasing decisions. Thisresearch focuses on users of the Netflix pay TVservice. This research was conducted in Bekasi City,which is an area with quite a lot of Netflix users. Thisresearch will use a quantitative approach with theuser population in Bekasi City.